Plasmid pUM505 encodes a Toxin–Antitoxin system conferring plasmid stability and increased Pseudomonas aeruginosa virulence. (November 2017) - Hernández-Ramírez, K.C.; Chávez-Jacobo, V.M.; Valle-Maldonado, M.I.; Patiño-Medina, J.A.; Díaz-Pérez, S.P.; Jácome-Galarza, I.E.; Ortiz-Alvarado, R.; Meza-Carmen, V.; Ramírez-Díaz, M.I.
Abstract: Pseudomonas aeruginosa plasmid pUM505 possesses a pathogenicity island that contains the pumAB genes that encode products with sequence similarity to Toxin–Antitoxin (TA) modules. RT-PCR assays on the overlapping regions of the pumAB genes generated a bicistronic messenger RNA, suggesting that they form an operon. When the pumAB genes were cloned into the pJET vector, recombinant plasmid pJET- pumAB was maintained under nonselective conditions in Escherichia coli cells after six daily subcultures, whereas pJET without pumAB genes was lost. These data indicate that pumAB genes confer post-segregational plasmid stability. In addition, overexpression of the PumA protein in the E. coli BL21 strain resulted in a significant growth inhibition, while BL21 co-expressing the PumA and PumB proteins did not show growth inhibition. These results indicate that pumAB genes encode a TA system where the PumB protein counters the toxic effects of the PumA toxin. Furthermore, P. aeruginosa PAO1 transformants with the pumA gene increased Caenorhabditis elegans and mouse mortality rate and improved mouse organ invasion, effects neutralized by the PumB protein. Moreover, purified recombinant His-PumA protein decreased the viability of C. elegans, indicating that the PumA protein could acts as a toxin. These results indicate that PumA has the potential to promoter the PAO1 virulence against C. elegans and mice when is expressed in absence of PumB. This is the first description, to our knowledge, of a plasmid-encoded TA system that confers plasmid stability and encoded a toxin with the possible ability to increase the P. aeruginosa virulence. Highlights: pUM505 contains the pumAB genes that encode a non conventional TA system. The PumAB TA system plasmid-encoded confers plasmid stability. The PumA protein has the potential to increase the virulence of Pseudomonas aeruginosa. PumB protein neutralizes the negative effects of PumA protein.